Lecture summaries (Proceedings of the Society of Antiquaries of Scotland, 1989)
Five lecture summaries:Elginhaugh: A Roman fort and its environsThe greater medieval burgh kirksWilliam Elphinstone, bishop and founder of the University of AberdeenScottish graveyardsA hard-won wilderness: man and environment on Foula, Shetland and Western Faroe